Prospects in Broadening the Application of Planar Solution-Based Distributed Bragg Reflectors - Palo Emilia; Daskalakis Konstantinos S.S (WILEY, 2025)
Distributed Bragg reflectors (DBRs) are primarily used in lasers and telecommunications. Liquid film deposition of DBRs holds great promise for expanding their utilization in environmental friendly, low-cost, and large-area applications. In this perspective, this work reviews the progress in solution-based DBR research and evaluates their application in light-emitting devices, photovoltaics and sensing. For these applications, a high refractive index contrast between the alternating layers of a DBR is important for achieving high reflectivity from only a small number of layers. While there is a plethora of solution processes that can produce low-refractive index films, the realization of high-refractive index films is challenging. Recent advances in materials and coating processes have addressed this challenge and novel solution-based DBRs showed remarkable performance which is on par with traditional physical/chemical vapor phase deposition. This work examines what inhibits solution-based DBRs, despite the great progress, to reach the stage of commercial application. In addition, this work found that DBR research is substantially extended beyond photonics, thus by summarizing materials and processes in a single table it aims to provide the necessary information to researchers with diverse backgrounds.